House of bamboo [videorecording (DVD)] - Fuller, Samuel, 1912-1997; Fuller, Samuel, 1912-1997; Ryan, Robert, 1909-1973; Stack, Robert, 1919-2003; Yamaguchi, Yoshiko, 1920-2014; Mitchell, Cameron, 1918-1994 (Fox film noir, 2005)
"Sandy Dawson has assembled a platoon of ex-Army thugs to run pachinko parlors while pulling off bloody heists and armed robbery. The murder of a friend brings Eddie Spanier into the group, along with his beautiful mistress. But Spanier's behavior grows treacherous, and his loyalties become questionable, leading to a breathless, murderous conclusion high above the ancient city of Tokyo."--Container.